A low-cost bilirubin measurement tool for neonatal jaundice monitoring at the point-of-care: a comparison of BiliDx with a standard laboratory bilirubinometer and transcutaneous bilirubinometer. Issue 1 (March 2021) - Shapiro, Alyssa; Anderson, Jessica; Bond, Meaghan; Schwarz, Richard; Carns, Jennifer; Mtenthaonga, Prince; Kumwenda, Watson; Johnston, Ryan; Miros, Robert; Dube, Queen; Chiume, Msandeni; Richards-Kortum, Rebecca
Abstract: Background: Neonatal jaundice, defined as an excess of bilirubin in blood at birth or shortly thereafter, has a disproportionately high impact in low-resource settings. Three quarters of deaths from jaundice occur in sub-Saharan Africa and south Asia. Jaundice is easily treated with blue light phototherapy; however, accurate, low-cost bilirubin monitoring is essential to guide effective phototherapy treatment in low-resource settings. To address this need, we developed BiliDx, a low-cost, portable reader that quantifies bilirubin concentration in a few drops of blood applied to a lateral flow card. BiliDx measures absorbance at three wavelengths: blue (bilirubin), amber (haemoglobin interference), and red (background) and can perform measurements in less than 5 mins at the point of care, without the need for a costly centrifuge or extensive training. Here, we compare the accuracy of BiliDx against a standard laboratory bilirubinometer and a transcutaneous bilirubinometer. Methods: This study took place in two central hospitals in Malawi. We included samples from neonates being treated in neonatal wards and deemed to be at risk for jaundice or who were undergoing phototherapy. Guardians provided written informed consent. We measured bilirubin using three devices: BiliDx, a bilirubinometer (Reichert UNISTAT), and a transcutaneous bilirubinometer (Drager JM-105), with a total of 475 measurements per device. Training (149 measurements) and validation (326 measurements) sets were created by ordering the first measurement per patient from lowest to highest UNISTAT bilirubin; every third measurement was selected for the training set. The training set was used to fit a model that correlated bilirubin concentration to absorbances at three wavelengths. The validation set was used to make an unbiased evaluation of the accuracy of the model. Findings: We enrolled 456 neonates between August 7 and December 12, 2019; 247 of 326 (75%) of BiliDx measurements in the validation set were within 2 mg/dL of UNISTAT measurements, compared with 44 of 281 (6%) of quantitative transcutaneous measurements. No adverse events occurred. Interpretation: BiliDx can provide accurate bilirubin monitoring. BiliDx is more accurate than transcutaneous bilirubinometry, a technology often endorsed for its non-invasive, portable nature. Limitations include that only ten nurses used BiliDx and only central hospitals were included. Testing of the BiliDx device is ongoing; we aim to collect enough measurements >20 mg/dL to assess the accuracy of BiliDx over the intended bilirubin concentration range of 0–35 mg/dL. Future studies will evaluate usability among a larger group of nurses and hospital settings. Funding: USAID Saving Lives at Birth Award No. 7200AA18FA0016.